Gelatin-based hemostatic agents for medical and dental application at a glance: a narrative literature review - Irfan, Nining Irfanita; Suwandi, Asrul; Mohd Zubir, Amir Zulhakim; Haris @ Harith, Muhammad Salahuddin; Jaswir, Irwandi; Lestari, Widya (Elsevier B.V., 2022)
Uncontrolled bleeding is linked to higher treatment costs, risk of post-surgical infection and increased disease and death. Hemostatic agents are used to treat excessive bleeding. A good hemostatic agent controls bleeding effectively, reduces the need for blood transfusion, removes the need for systemic drugs to control bleeding, results in shorter surgery time, and reduces the cost and length of hospital stay of the patient. Gelatin-based hemostatic agents have been widely used in medical and dental procedures, owing to their biodegradability and biocompatibility, as well as availability and low cost of raw materials. In this narrative literature review, we discuss the back- ground and different types of gelatin-based hemostatic agents in medical and dental procedures, the comparison of gelatin-based and non-gelatin-based hemostatic agents, and the usage and develop- ment of enhanced or novel gelatin-based hemostatic agents. Gelatin-based hemostatic agents are effective and important part of bleeding control, as evidenced by its wide application in medicine